2017
DOI: 10.1111/jcpp.12807
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and friendships among eight‐year‐old children: time‐trends over a 24‐year period

Abstract: Loneliness was a common phenomenon in childhood, and no notable changes were found during the 24-year study period. Psychiatric symptoms were strongly associated with loneliness. It is important to pay attention to children's loneliness and make it an integral part of school health care. Further epidemiological research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 32 publications
3
36
0
1
Order By: Relevance
“…Attending to the dimensions of isolation in relation to those pertaining to attitudes towards physical education, it is observed that when emotional isolation increases in students, the rating that they attribute to the subject and teacher is lower [77,78], and they report less agreement with respect to subject management [79,80]. However, we demonstrate that this is not a specific aspect directed towards the teacher or this subject but is a trait that these types of students maintain towards teaching staff and all subjects generally speaking [81].…”
Section: Discussionmentioning
confidence: 99%
“…Attending to the dimensions of isolation in relation to those pertaining to attitudes towards physical education, it is observed that when emotional isolation increases in students, the rating that they attribute to the subject and teacher is lower [77,78], and they report less agreement with respect to subject management [79,80]. However, we demonstrate that this is not a specific aspect directed towards the teacher or this subject but is a trait that these types of students maintain towards teaching staff and all subjects generally speaking [81].…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study among 8-9-year-olds found no substantial change in the prevalence of loneliness 1989-2013. 10 A study from US found a decline in loneliness over time in college and high school students (1991-2012) 11 and a study from the Philippines found increasing prevalence of loneliness among adolescents 2003-2011. 12 The aetiology of loneliness among children and adolescents is complex.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 A study from Finland showed increasing odds for loneliness by decreasing parental education among 8-9-year-old children. 10 A study of Hungarian adolescents found that loneliness was associated with low subjective socioeconomic status, parental unemployment and low educational attainment. 20 A study from USA 21 found that high family income participants were more likely to experience a trajectory of stable, low loneliness compared to trajectories of increasing and chronic high loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…From an applied perspective, the study of loneliness is important because there is a high prevalence (20%) of chronic loneliness during elementary school (Lempinen, Junttila, & Sourander, 2018), and children who report high levels of loneliness experience school-related disadvantages and also suffer from emotional, mental, and physical problems (Heinrich & Gullone, 2006).…”
mentioning
confidence: 99%